O uniwersalności zajęć teatralnych w pracy z dziećmi i młodzieżą = On universality of theatre classes in working with children and teenagers - Prokosz, Małgorzata (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Theatre education is an underestimated field of cultural education of children and teenagers. In this article the Author indicates the potential of classes oscillating around the issue of the theatre. She also gives examples of practical forms of classes that can be implemented at any educational institution.
Keywords: teatr; aktywność twórcza; edukacja kulturalna; edukacja teatralna; formy zajęć teatralnych; theatre; creative activity; cultural education; theatre education; forms of theatre classes